Resources utilization in maize (Zea mays)-based intercropping system under rainfed condition - Solanki, N S; Singh, Dilip; Sumeria, H K (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was conducted during rainy (kharif) seasons of 2007 and 2008 at Rajasthan College of Agriculture, Udaipur to work out radiation and rain water-use efficiency under various maize (Zea mays L.)-based intercropping systems. The treatments consisting of sole maize, sole blackgram (Vigna mungo L.), sole greengram (Vigna radiata L.), sole soybean [Glycine max (L.), Merr.], maize + blackgram (2:2), maize + greengram (1:1) and maize + soybean (1:1). The results indicated that radiation-use efficiency of sole maize varied from 0.47 to 0.92 g/MJ, whereas, in intercropping system with blackgram, greengram and soybean, it varied from 0.55 to 1.03 g/MJ, 0.69 to 1.03 g/MJ and 0.79 to 1.32 g/MJ, respectively. The highest radiation-use efficiency of 1.32 g/MJ was recorded under maize + soybean (1:1) intercropping, followed by maize + greengram and maize +blackgram (1.03 g/MJ). The highest rain water-use efficiency was recorded under maize + blackgram (15.56 kg grain/ha/mm), followed by maize + soybean (14.08 kg grain/ha/mm) and maize + greengram (13.52 kg grain/ha/mm). The highest maize grain equivalent yield of 5.381 and 4.948 tonnes/ha was recorded under maize + blackgram (2:2) intercropping during 2007–2008, respectively which was significantly superior over sole maize by 21.1 and 12.4%.